Evidence for Secondary Ice Production in Southern Ocean Maritime Boundary Layer Clouds. Issue 16 (16th August 2022) - Järvinen, Emma; McCluskey, Christina S.; Waitz, Fritz; Schnaiter, Martin; Bansemer, Aaron; Bardeen, Charles G.; Gettelman, Andrew; Heymsfield, Andrew; Stith, Jeffrey L.; Wu, Wei; D'Alessandro, John J.; McFarquhar, Greg M.; et al.
Abstract: Maritime boundary‐layer clouds over the Southern Ocean (SO) have a large shortwave radiative effect. Yet, climate models have difficulties in representing these clouds and, especially, their phase in this observationally sparse region. This study aims to increase the knowledge of SO cloud phase by presenting in‐situ cloud microphysical observations from the Southern Ocean Clouds, Radiation, Aerosol, Transport Experimental Study (SOCRATES). We investigate the occurrence of ice in summertime marine stratocumulus and cumulus clouds in the temperature range between 6 and −25°C. Our observations show that in ice‐containing clouds, maximum ice number concentrations of up to several hundreds per liter were found. The observed ice crystal concentrations were on average one to two orders of magnitude higher than the simultaneously measured ice nucleating particle (INP) concentrations in the temperature range below −10°C and up to five orders of magnitude higher than estimated INP concentrations in the temperature range above −10°C. These results highlight the importance of secondary ice production (SIP) in SO summertime marine boundary‐layer clouds. Evidence for rime splintering was found in the Hallett‐Mossop (HM) temperature range but the exact SIP mechanism active at lower temperatures remains unclear. Finally, instrument simulators were used to assess simulated co‐located cloud ice concentrations and the role of modeled HM rime‐splintering. We found that CAM6 is deficient in simulating number concentrations across the HM temperature range with little sensitivity to the model HM process, which is inconsistent with the aforementioned observational evidence of highly active SIP processes in SO low‐level clouds. Plain Language Summary: Clouds in the Southern Ocean are important for climate but not well represented in climate models. Observations in this remote region have been rare. This study presents results from a recent airborne campaign that took place in the Southern Ocean where low‐ and mid‐level clouds were investigated by detecting individual cloud particles within the clouds. Although large fraction of the observed clouds did not contain ice crystals, occasionally high amounts of ice crystals were observed that cannot be explained by ice formation on aerosol particles but were result of multiplication of existing ice crystals. We tested the capability of a commonly used climate model to represent the observed ice concentrations and their sensitivity to one ice multiplication process parameterized in the model. These investigations revealed that the in the model the ice multiplication process was not responsible for generation of ice, which is in contradiction with the observations. Key Points: Ice concentrations several orders of magnitude higher than ice nucleating particle concentrations were observed Secondary ice production was believed to be responsible for the observed high ice number concentrations Comparison with climate model indicated that secondary ice processes are still inadequately represented in the model